The Flight Mechanism of a Bird-like Flapping Wing Robot at a Low Reynolds Number - Changtao Ding; Xiating Yao; Chengyao Liu (Journal of Robotics)
The flight mechanism of a bird-like flapping wing robot at a low Reynolds number was studied in this study for improving the robot performances. Both the physical model and the kinematic model were first established. The dynamic model of the robot at a low Reynolds number was built with the RANS (Reynolds-averaged Navier-Stokes) equations and the Spalart-Allmaras turbulence model. The flight experiments were carried out and the results were discussed. Lift and drag coefficient curves show that it generates upward lift and forward thrust in the phase that the wing flaps downwards, the rate of the coefficient curves is the biggest when the flapping direction changes. Pressure contours indicate that small vortexes with high pressure values appear at the wing edges. There are four velocity vortex groups in total at the front and back of the wing in the velocity contours. Some methods for improving the robot flight efficiency and the robot strength as well as the stitching position of the robot skin have been obtained from the above results. The methods provide the important guidance for the stable flights of the flapping wing robot with the high efficiency.